2013
DOI: 10.3389/fpls.2013.00317
|View full text |Cite
|
Sign up to set email alerts
|

In silico comparison of genomic regions containing genes coding for enzymes and transcription factors for the phenylpropanoid pathway in Phaseolus vulgaris L. and Glycine max L. Merr

Abstract: Legumes contain a variety of phytochemicals derived from the phenylpropanoid pathway that have important effects on human health as well as seed coat color, plant disease resistance and nodulation. However, the information about the genes involved in this important pathway is fragmentary in common bean (Phaseolus vulgaris L.). The objectives of this research were to isolate genes that function in and control the phenylpropanoid pathway in common bean, determine their genomic locations in silico in common bean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 66 publications
3
32
0
Order By: Relevance
“…The MLO distribution supported the high level of micro- and macro-synteny that exist between legume genomes 38 39 . It also further illustrated the assumption that most legume genes are likely located in syntenic regions 40 as previously demonstrated for most phenylpropanoid genes of soybean and common bean 41 . This distribution also suggested that they mainly arose from segmental duplication as it was already assumed for rice and several Rosaceae species 17 42 .…”
Section: Discussionsupporting
confidence: 78%
“…The MLO distribution supported the high level of micro- and macro-synteny that exist between legume genomes 38 39 . It also further illustrated the assumption that most legume genes are likely located in syntenic regions 40 as previously demonstrated for most phenylpropanoid genes of soybean and common bean 41 . This distribution also suggested that they mainly arose from segmental duplication as it was already assumed for rice and several Rosaceae species 17 42 .…”
Section: Discussionsupporting
confidence: 78%
“…The physical location of P based on our map is between the SNPs ss715649622 and ss715649327, which are at 11,251,772 and 11,388,741 base pairs (bp), respectively (see Song et al, 2015 supplemental files for physical location of SNPs). This falls within the rather broad range of 3.5 to 31.1 Mb identified by Reinprecht et al, (2013) for the location of P. Moghaddam et al, (2014) recently suggested that the underlying sequence for P consists of two gene models (Phvul.007G171300 and Phvul.007G171400) corresponding to an A. thaliana basic helix-loop-helix sequence and encompassing a region from 40,383,553 to 40,397,270 bp. The %28 Mb difference in location corresponds to %17 cM in our map.…”
Section: Discussionmentioning
confidence: 59%
“…shown that J is linked to a region containing MYB123 [26], similar to TT2 in Arabidopsis thaliana (AT5G35550.1) [27] and Glycine max [26], which acts as a key determinant in the proanthocyanidin accumulation of a developing seed [27].…”
Section: Biochemical Nature Of Seed Coat Glossiness and Its Implicatimentioning
confidence: 99%